A Study on Communal Life of Pakhtūn Women in Sīrah Perspective - Khan, Javed; Ahmed, Muhammad Mushtaq; Khan, Abzahir (Journal of Islamic and Religious Studies, 2019)
Women play a role of paramount importance in the establishment of a distinctive nature of society. Women in Pakhtūn society are regarded with respect and piety. Pakistanis in general and Pakhtūn nation in particular can tolerate monetary losses, owing to their women but they cannot tolerate immoral and disgraceful events attached with their women (mothers, sisters, wives, and daughters) which most often become a reason for the domestic enmities and hostilities. In this article, efforts were made to answer the questions; that whether the different aspects of female lives have been treated according to the teachings of Sīrah or religion is used only as a weapon to suppress them and snatch their rights. The purpose of the study was to investigate the social issues of women from birth related ceremonies, assigning names, training and education, marriage, life after marriage and heredity related issues to their domestic routine issues and how to solve these issues in the light of teachings of the Prophet (P.B.U.H)? Furthermore, suggestions were given to make these solutions more effective and easy to be implemented in our society.